Axotomy Leads to Reduced Calcium Increase and Earlier Termination of CCL2 Release in Spinal Motoneurons with Upregulated Parvalbumin Followed by Decreased Neighboring Microglial Activation - Paizs, Melinda; Patai, Roland; I. Engelhardt, Jozsef; Katarova, Zoya; Obal, Izabella; Siklos, Laszlo (CNS & Neurological Disorders - Drug Targets, 2017)
Background: Motoneurons with naturally elevated calcium binding protein content, such as parvalbumin, are more resistant against injury. Furthermore, increase of intracellular calcium, which plays a pivotal role in injury of neurons, could be moderated by elevating their calcium binding proteins. Objective: To test whether by elevating parvalbumin content of motoneurons, activation of neighboring microglial cells, a robust component of the inflammatory reaction after injury, could be influenced. Methods: Mice overexpressing neuronal parvalbumin were derived and the spinal motoneurons were challenged by cutting the sciatic nerve. At postoperative days 1, 4, 7, 14 and 21 the change of the chemokine ligand 2 immunostaining in the motoneurons and the activation of microglial cells, measured as alterations in CD11b immunostaining were determined. Calcium level of motoneurons was tested electron microscopically at postoperative day 7. Results: After axotomy, increased level of chemokine ligand 2 was detected in the lumbar motoneurons. The staining intensity reached its maximum at day 7 and decayed faster in transgenic mice compared to controls. Microglial activation around motoneurons attenuated faster in parvalbumin overexpressing mice, too, but the decrease of microglial activation was delayed compared to the decline of the chemokine ligand 2 signal. At the time when the microglial reaction peaked, no intracellular calcium increase was detected in the motoneurons of transgenic mice, in contrast to the twofold increase in wild type animals. Conclusion: Increased calcium buffering capacity, which augments resistance of motoneurons against calcium-mediated injury, leads to earlier termination of motoneuronal emission of CCL2 followed by a reduction of neighboring microglial activation after axotomy.
Keywords: calcium binding protein